Development Of Students' Podcast Skills as Part of Lecturer's Teaching Variation to Improve Students' Digital Communication - Mesra, Romi; Monica, Waode Santa; Apada, A. Magfira Satya (Abdi Masyarakat, 2024)
This study aims to develop students' podcast skills as part of teaching variations to enhance digital communication capabilities in the industrial revolution 4.0 era. The method employed a structured approach consisting of four main stages: preparation, implementation, practice, and evaluation. The program was conducted at the Sociology Education Study Program, Manado State University, involving 25 students as participants. The preparation stage included needs assessment and learning module design. The implementation stage focused on theoretical understanding and technical skills development. The practice stage involved group projects where students created their podcast episodes, while the evaluation stage assessed both technical and content aspects of the produced podcasts. Results showed significant improvement in students' podcast skills, demonstrated by the increase in test scores from an average of 31.72 in the pretest to 80.56 in the posttest. The evaluation revealed that students successfully developed competencies in podcast production, from conceptualization to final editing. Additionally, participants showed enhanced abilities in digital communication, teamwork, and content creation. This program proved effective in developing students' digital communication skills while providing practical experience in modern content creation.